The 7 : seven wonders that will change your life - Beck, Glenn (Threshold Editions/Mercury Radio Arts, 2011)
Radio and television personality and bestselling author Beck, together with psychiatrist Ablow, shares the inspirational story of the seven simple principles that changed Beck's life.